Potent Cas9 Inhibition in Bacterial and Human Cells by AcrIIC4 and AcrIIC5 Anti-CRISPR Proteins - Jooyoung Lee (American Society for Microbiology, 2018)
ABSTRACT In their natural settings, CRISPR-Cas systems play crucial roles in bacterial and archaeal adaptive immunity to protect against phages and other mobile genetic elements, and they are also widely used as genome engineering technologies. Previously we discovered bacteriophage-encoded Cas9-specific anti-CRISPR (Acr) proteins that serve as countermeasures against host bacterial immunity by inactivating their CRISPR-Cas systems (A. Pawluk, N. Amrani, Y. Zhang, B. Garcia, et al., Cell 167:1829–1838.e9, 2016, https://doi.org/10.1016/j.cell.2016.11.017). We hypothesized that the evolutionary advantages conferred by anti-CRISPRs would drive the widespread occurrence of these proteins in nature (K. L. Maxwell, Mol Cell 68:8–14, 2017, https://doi.org/10.1016/j.molcel.2017.09.002; A. Pawluk, A. R. Davidson, and K. L. Maxwell, Nat Rev Microbiol 16:12–17, 2018, https://doi.org/10.1038/nrmicro.2017.120; E. J. Sontheimer and A. R. Davidson, Curr Opin Microbiol 37:120–127, 2017, https://doi.org/10.1016/j.mib.2017.06.003). We have identified new anti-CRISPRs using the same bioinformatic approach that successfully identified previous Acr proteins (A. Pawluk, N. Amrani, Y. Zhang, B. Garcia, et al., Cell 167:1829–1838.e9, 2016, https://doi.org/10.1016/j.cell.2016.11.017) against Neisseria meningitidis Cas9 (NmeCas9). In this work, we report two novel anti-CRISPR families in strains of Haemophilus parainfluenzae and Simonsiella muelleri, both of which harbor type II-C CRISPR-Cas systems (A. Mir, A. Edraki, J. Lee, and E. J. Sontheimer, ACS Chem Biol 13:357–365, 2018, https://doi.org/10.1021/acschembio.7b00855). We characterize the type II-C Cas9 orthologs from H. parainfluenzae and S. muelleri, show that the newly identified Acrs are able to inhibit these systems, and define important features of their inhibitory mechanisms. The S. muelleri Acr is the most potent NmeCas9 inhibitor identified to date. Although inhibition of NmeCas9 by anti-CRISPRs from H. parainfluenzae and S. muelleri reveals cross-species inhibitory activity, more distantly related type II-C Cas9s are not inhibited by these proteins. The specificities of anti-CRISPRs and divergent Cas9s appear to reflect coevolution of their strategies to combat or evade each other. Finally, we validate these new anti-CRISPR proteins as potent off-switches for Cas9 genome engineering applications. IMPORTANCE As one of their countermeasures against CRISPR-Cas immunity, bacteriophages have evolved natural inhibitors known as anti-CRISPR (Acr) proteins. Despite the existence of such examples for type II CRISPR-Cas systems, we currently know relatively little about the breadth of Cas9 inhibitors, and most of their direct Cas9 targets are uncharacterized. In this work we identify two new type II-C anti-CRISPRs and their cognate Cas9 orthologs, validate their functionality in vitro and in bacteria, define their inhibitory spectrum against a panel of Cas9 orthologs, demonstrate that they act before Cas9 DNA binding, and document their utility as off-switches for Cas9-based tools in mammalian applications. The discovery of diverse anti-CRISPRs, the mechanistic analysis of their cognate Cas9s, and the definition of Acr inhibitory mechanisms afford deeper insight into the interplay between Cas9 orthologs and their inhibitors and provide greater scope for exploiting Acrs for CRISPR-based genome engineering.